HUBUNGAN PERAN ORANG TUA DENGAN PENGETAHUAN DAN SIKAP ANAK USIA SEKOLAH DALAM MELAKUKAN PENCEGAHAN KEKERASAN SEKSUAL - wulan khairini (Universitas Wiralodra, 2019)
School-aged children are at risk of sexual abuse, but this sexual abuse is preventable. One way of prevention is to increase the role of parents as educators. This study aims to determine the relationship between the role of parents with knowledge and attitude of AUS in preventing sexual abuse. The research design used is descriptive correlation by using cross sectional approach. This research was conducted at state elementary school 38 Pekanbaru in May 2018 with sample amounted to 124 people. The result of univariate analysis was found that most of the parents had good role which was 63 people (50,8%), with good knowledge of school-aged children was 78 (62,9%) and good attitude of school-aged children was 83 people (66,9%). Chi-Square test results there is a significant relationship between the role of parents with knowledge of school-aged children with the value of p value = 0.026 <0.05 and there is a significant relationship between the role of parents with attitude of school-aged children with value p value = 0.031 <0.05. It is expected that parents run the role as educators well so as to improve knowledge and attitude of school-aged children in obtaining sex education.